THE DEVELOPMENT OF MUSICAL INTELLIGENCE IN JUNIOR SCHOOLCHILDREN DURING THE LESSONS OF THE ARTISTIC CYCLE - Lazarenko, Natalia; Brovchak, Liudmyla; Starovoit, Lesia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The relevance of the research is due to the necessity of implementation of the person-oriented approach into the educational process with the aim to provide the development of musical intelligence in junior schoolchildren on the basis of determining their individual peculiarities, forming their cognitive and communicative skills. Due to this, basic approaches to understanding and interpretation of the notion “intelligence” have been analyzed; scientific researches concerning the issue of the development of musical intelligence of children have been processed. The aim and objectives of the article, which consist in processing the dynamics of the development of musical intelligence of children in the process of artistic activities, have been set. Pedagogical conditions of the development of musical intelligence of children during the process of artistic activity have been singled out, the dynamics of the development of musical intelligence during the lessons of artistic cycle has been discovered in junior preschoolers with the help of testing and musical and creativity activities, degrees of studied qualities  development have been compared in children of control and experimental groups, results of summative and final tests have been compared.  It has been established, that without observance of special psychological and pedagogical conditions and without purposeful mental impact the development of musical intelligence in junior schoolchildren will have no effect, because changes that occur during the training in accordance with the traditional approach are random in most cases and cannot guarantee the effectiveness of children`s development.